CEUS in diagnosis of renal masses - Ochyra, Łukasz; Łopuszyńska, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Contrast enhanced ultrasound (CEUS) is a modern diagnostic method that uses ultrasound waves in combination with intravenous administration of a contrast agent. It enables obtaining high resolution and assessing microcirculation in real time, thanks to which the researcher is able to analyze the enhancement and its features, which may help in diagnosing a specific pathology. Contrast agents, similar to CT and MRI, show specific phases of enhancement after administration - arterial, venous, delayed. Their additional advantage is safety, especially for patients with impaired kidney and thyroid function, and causing fewer allergic reactions. The aim of this review is to present the CEUS examination technique and the latest reports in the field of diagnosis of renal lesions. Material and methods This review was prepared based on the literature available from recent years in the PubMed and Google Scholar scientific databases using the keywords: ultrasonography, contrast enhanced ultrasonography, kidney, renal masses. Results Studies show that CEUS can be an effective method for imaging both cystic and solid lesions in the kidney. When using a contrast agent, the lesions show characteristic features that can guide the investigator to the diagnosis. Moreover, in comparative analyses, CEUS achieved comparable or better results than other diagnostic imaging methods. Conclusions CEUS is a modern and promising diagnostic method that can successfully compete with CT and MRI. Moreover, the metabolism and pharmacokinetics of contrast agents and their safety mean that CEUS can be used for the diagnosis of unclear pathologies in elderly patients, as well as for the control and supervision of changes that require frequent imaging. Keywords: ultrasonography, contrast enhanced ultrasonography, kidneys, renal masses